(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines the strategic objectives of raising the spiritual maturity of the individual at a new stage of development of Uzbekistan, the social goals of education and upbringing policy, as well as current socio-philosophical problems of raising the spiritual culture of the individual and their solutions.